Emerging ecological trends in West Africa: implications on soil organic matter and other soil quality indicators - Mesele, S.A.; Ocansey, C.M.; Bougma, A.; Azeez, J.O.; Ajiboye, G.A.; Logah , V.; Compaore, H.; Veenendaal, E.M.; Lloyd, J. (Springer, 2024)
Aims In West Africa, savannas are changing to either forest islands or arable lands arising from anthropogenic interference with the natural ecosystem. This study aimed at quantifying the trade-offs of this land use conversion on major soil quality indicators.